Ours must be a nation of an empowered people : the inauguration of President Fidel V. Ramos, Vice President Joseph E. Estrada the commemorative inaugural book. ([Manila, Philippines] : [publisher not identified], 1993)
We present this book as gift to the next generation Filipinos. They too can cherish that moment in time when the torch of freedom and of hope blazed brilliantly in our country, when democracy was in full bloom and its shining glory on June 30, 1992.
Chapter 1 : The Saga of the Philippine Presidency Chapter 2 : His Excellency FIDEL V. RAMOS Chapter 3 ; Vice President JOSEPH E. ESTRADA Chapter 4 : The Inaugural Chapter 5 : What they say about Fidel V. Ramos
"Commemorative inaugural book."
Keywords: PHILIPPINES -- POLITICS AND GOVERNMENT